Super Life Span Theory and Its Implications in Career Guidance and Counseling in Schools - Eki Aprinaldi; A Muri Yusuf; Afdal Afdal (Jurnal Neo Konseling, 2021)
Based on the findings in the field, there are still many students who after graduating from school are confused about finding work and are not comfortable with their work, so that individuals often quit their jobs because they are not comfortable and are not satisfied with their work. The method used in analyzing the problem is a literature study obtained from books, articles, and scientific journals that are relevant to the problems being analyzed. From this analysis, it was found that Super life span theory is a theory that explores career development throughout the life span, which in this theory explains that individuals are said to be mature or ready to make career decisions if their knowledge to make career decisions is supported by adequate information about work based on explorations. have been done. So it is very necessary to be understood by guidance and counseling teachers in order to support the understanding and career development of students. This theory can be applied in services by guidance and counseling teachers in schools which are designed based on the needs of students who are the target of services that can support the achievement of direction, determination and career development of students in the future.